Seen and Unseen - Flanagan, K. author. aut Link
XII, 251 p.
Keywords: This lively and highly original study explores the link between visual culture and religion in terms of tales, memory and character. It draws out the sociological implications of handling the virtual and virtue in ways of seeing. Using Simmel's approach to religiosity in his third study of sociology in theology, Flanagan explores how spectacle is to be understood in ways that yield trust. The study will be invaluable for undergraduate and postgraduate courses on visual culture, sociology of religion and theology.